Beyond 'More Crop per Drop' : Evolving Thinking on Agricultural Water Productivity - Giordano, Meredith; Turral, Hugh; Scheierling, Susanne M.; Tréguer, David O.; McCornick, Peter G. (Colombo, Sri Lanka: International Water Management Institute, and Washington, DC: World Bank, 2017)
This report aims to provide key highlights from two decades of IWMI research and the broader irrigation literature on agricultural water productivity, with an emphasis on the evolution and application of the concept, highlighting its contributions and limitations while identifying opportunities for further refinements in the way it is understood and applied. Chapter two describes the origins of the concept of agricultural water productivity and its methodological developments. Chapter three illustrates the different ways the concept has been operationalized in applied research, offers a description of the pathways—with their associated interventions, for improving water productivity, and discusses the contributions to broader development objectives. Based on these, and considering the broader literature, Chapter four presents a set of key lessons and insights from two decades of research on water productivity. Chapter five concludes by highlighting how a focus on agricultural water productivity has brought greater attention to critical water scarcity and management issues. Important strategic opportunities remain, however, for continued improvements in technologies and management practices, data sources, and interdisciplinary research to develop and apply more comprehensive approaches to address water scarcity concerns and, ultimately, make progress towards broader development objectives.